2017
DOI: 10.1002/cphc.201700446
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of the Reaction Products between the Criegee Intermediate CH2OO and HCl

Abstract: Pulsed Fourier-transform microwave experiments have been performed to probe the products resulting from the reaction between HCl and the simplest Criegee intermediate, CH OO, where the reaction is considered to be important in atmospheric chemistry. The experimentally determined rotational parameters interpreted with the help of quantum chemical calculations support the identification of chloro-methyl hydroperoxide molecule as the primary product of this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…This indicates that the pre-reactive complex in the latter two reactions promptly reacts, in agreement with low reaction barrier predicted by theoretical calculations [68,117,143]. No systematic experiments have been performed for yield measurement of MFOHPs at ambient conditions from the insertion reactions.…”
Section: Figuresupporting
confidence: 80%
See 1 more Smart Citation
“…This indicates that the pre-reactive complex in the latter two reactions promptly reacts, in agreement with low reaction barrier predicted by theoretical calculations [68,117,143]. No systematic experiments have been performed for yield measurement of MFOHPs at ambient conditions from the insertion reactions.…”
Section: Figuresupporting
confidence: 80%
“…They were also able to observe decomposition of one of the HPMF conformers to formic acid anhydride, consistent with previous static chamber studies. Endo and co-workers have observed MFOHP products from CH2OO + HCl [143], CH2OO + HCOOH [144] and CH2OO + H2O/(H2O)2 [101] reactions using Fourier transform microwave spectroscopy. They were also able to observe pre-reactive complex formation in the CH2OO + H2O/(H2O)2 reaction system [142], as shown in Figure 9, but not in the CH2OO + HCl [143] and CH2OO + HCOOH reaction systems [144].…”
Section: Figurementioning
confidence: 99%
“…In reactions with CO, NO, SO 2 , and NO 2 , ,,, CI acts as an oxygen atom donor. In reactions with atmospheric species contain hydrogen atoms, such as H 2 O, NH 3 , CH 4 , HCl et al, ,, it inserts itself into the O–H, N–H, or C–H bond, forming a substituted peroxide. All of these possible reaction mechanisms have been applied to the CI + acrolein reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent reaction and formation of the alkoxy radical would be expected to yield a carbonyl and NO 2 . The main products of reaction of SCI with the inorganic acid HCl have been predicted to be chlorohydroperoxides (Reaction R10) (Foreman et al, 2016;Vereecken, 2017), with these products observed experimentally for CH 2 OO + HCl (Cabezas and Endo, 2017;Taatjes et al, 2021) and CH 3 CHOO + HCl (Cabezas and Endo, 2018). The main product of reaction with HNO 3 has been predicted to be hydroperoxy nitrates (Reaction R11) (Foreman et al, 2016;Raghunath et al, 2017;Vereecken, 2017).…”
Section: Bimolecular Reactions Of Scimentioning
confidence: 88%